Stygohydracarus karanovici sp.n., and Atractides inflatipes Lundblad, 1956, two water mites species (Acari: Hydrachnidia) from Montenegro (SE Europe) - Pesic, Vladimir M. (Zootaxa, 2001)
Two water mite species (Acari: Hydrachnidia) are reported from Montenegro (Yugoslavia, SE Europe). Stygohydracarus karanovici is described as a new species and Atractides inflatipes Lundblad, 1956 as the first record from the Balkan peninsula. The latter is a rare water mite species previously known only from the French Pyrenees.